Injectable hybrid system for strontium local delivery promotes bone regeneration in a rat critical-sized defect model - Ana Henriques Lourenço (Nature Portfolio, 2017)
Abstract Strontium (Sr) has been described as having beneficial influence in bone strength and architecture. However, negative systemic effects have been reported on oral administration of Sr ranelate, leading to strict restrictions in clinical application. We hypothesized that local delivery of Sr improves osteogenesis without eliciting detrimental side effects. Therefore, the in vivo response to an injectable Sr-hybrid system composed of RGD-alginate hydrogel cross-linked in situ with Sr and reinforced with Sr-doped hydroxyapatite microspheres, was investigated. The system was injected in a critical-sized bone defect model and compared to a similar Sr-free material. Micro-CT results show a trend towards higher new bone formed in Sr-hybrid group and major histological differences were observed between groups. Higher cell invasion was detected at the center of the defect of Sr-hybrid group after 15 days with earlier bone formation. Higher material degradation with increase of collagen fibers and bone formation in the center of the defect after 60 days was observed as opposed to bone formation restricted to the periphery of the defect in the control. These histological findings support the evidence of an improved response with the Sr enriched material. Importantly, no alterations were observed in the Sr levels in systemic organs or serum.